Association of Dyslipidemia, Oxidative Stress, and Inflammation With Redox Status in VLDL, LDL, and HDL Lipoproteins in Patients With Renal Disease. (November 2018) - Miljkovic, Milica; Stefanovic, Aleksandra; Simic-Ogrizovic, Sanja; Vekic, Jelena; Bogavac-Stanojevic, Natasa; Cerne, Darko; Kocbek, Petra; Marc, Janja; Jelic-Ivanovic, Zorana; Spasojevic-Kalimanovska, Vesna; Kotur-Stevuljevic, Jelena
Some cardiovascular complications in patients with chronic kidney disease and end-stage renal disease may be caused by structurally and functionally modified lipoproteins. Redox status (advanced oxidation protein products [AOPPs]), prooxidant–antioxidant balance, total protein sulfhydryl (SH-groups), and paraoxonase 1 (PON1) activity were assessed in 77 renal patients and 20 controls. Lipoproteins were isolated using ultracentrifugation. PON1, PON3, and pentraxin-3 concentration were determined by enzyme-linked immunosorbent assay (ELISA). Dyslipidemia-Oxy-Inflammation (DOI) score was calculated as a sum of dyslipidemia, oxidative stress, and inflammation scores. The dyslipidemia score ( P < .001), oxy score ( P < .01), inflammation score (P < .001), and the DOI score ( P < .001) were higher in patient groups compared with controls. The very-low-density lipoprotein (VLDL) fraction contained the highest amount of AOPP ( P < .001) compared with other lipoprotein fractions in all groups. The low-density lipoprotein (LDL) fraction contained elevated AOPP in all groups compared with the high-density lipoprotein (HDL) fraction ( P < .001). Significant positive correlation was observed between AOPP in LDL fraction and DOI score (ρ = 0.510, P < .01). Dyslipidemia, oxidative stress, and inflammation play an interactive role in renal disease and are mutually associated with redox status in VLDL, LDL, and HDL lipoproteins in plasma of renal patients.